Zipf Law Analysis of Urban Scale in China (Asian Journal of Social Science Studies, 2016)
In this paper, by using China's urban population data from 1990 to 2010 and double logarithmic regressionmodel to test China’s urban scale and urban rank through Zipf law, we found that China’s urban scaledistribution is relatively balanced, virtually conforming to Zipf's law. Researching and analyzing urban scaledistribution of China’s every province’s, we also found that the urban scale distributions of China’s all provincesare relatively complicated and they are not even close to 1. The increase of Zipf index means that urban scaledistribution is transiting from primacy degree distribution to ideal Zipf distribution. Further analyzing andcategorizing every province’s Zipf index, we can conclude that China’s urban scale distribution can becategorized four mainly: achieved ideal Zipf law; approaching to ideal Zipf distribution; The transition statefrom the primacy degree distribution to the Zipf law distribution; typical primacy degree distribution.